elaboração dos mapas de riscos dos laboratórios de Engenharia Elétrica – UFERSA/Campus Caraúbas - Carvalho, Samantha Kallydia Fernandes de (Universidade Federal Rural do Semi-Árido, 2018)
In view of the increasing number of accidents at work, it has been increasingly concerned with the work environment to which the worker is exposed. Occupational Health and Safety (OSH) has been gaining ground, with the development of preventive measures that promote the health and physical integrity of workers, always aiming at their well-being in order to perform better their functions and, consequently, generate better quality and productivity in their work environment. In laboratories with experimental practices focused on studies on electricity, it is noted the high risk of accidents. In such work, the mapping of the risks exposed in the Electrical Engineering laboratories of UFERSA - Caraúbas was carried out, when they were identified and classified in the environments, after which the Risk Maps of the laboratories under study were elaborated. Such maps serve to guide students, teachers, and other servers as to the dangers they are exposed to. Based on the data obtained, it was possible to observe that the laboratories meet the requirements described in NR 10 - Safety in Facilities and Services in Electricity, such as electrical grounding and deenergization procedures. However, in with regards to Personal Protection Equipment (PPE), there is a deficiency in use. For, however much the equipment is available, the standard is not fulfilled. It is necessary to raise awareness of the correct use of such EPIs for all the people who attend, showing the importance of the prevention of work accidents.
Monografia
Keywords: Eletricidade; Segurança do Trabalho; Prevenção; Riscos ocupacionais; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA